Circulating immune cells and risk of osteosarcoma: a Mendelian randomization analysis - Li, Lan; Sun, Yeqi; Luo, Jia; Liu, Mengjiao (Frontiers in Immunology, 2024)
Objectives: Osteosarcoma (OS) is the primary bone tumor originating from transformed mesenchymal cells. It is unclear whether associations between specific circulating immune cells and OS are causal or due to bias. To clarify whether predicted genetically altered circulating immune cells are associated with OS development, we performed a two-sample Mendelian randomization (MR) analysis.The genetic variants strongly associated with immune cell traits as instrumental variables (IVs) were used to perform MR analyses. The effect of specific immune cell on OS risk was measured using the summary statistics from the genome-wide association studies (GWAS).Our findings indicate that CD80 on CD62L+ myeloid dendritic cell and CD28-CD4-CD8-T cell absolute count are positively associated with OS (CD80 on CD62L+ myeloid dendritic cell, OR, 3.41, 95% CI, 1.40 to 8.31, P=0.007; CD28-CD4-CD8-T cell absolute count, OR, 4.49, 95% CI, 1.29 to 15.62, P=0.018). It is also found that a negative effect of CD20 on CD24+CD27+ B cell on OS (OR, 0.32, 95% CI, 0.14 to 0.72, P=0.006) and a similar impact of CD20 on IgD+ CD38-B cell on OS (OR, 0.19, 95% CI, 0.05 to 0.68, P=0.011).Conclusions: These findings illustrate that the genetic predisposition to specific immune cell can exert a causal effect on OS risk, which confirms the crucial role played by immunity in OS development. Particularly, the causal association between immune cells and OS underscores the evidence for exploring the new treatment strategy of OS in future.